Grandma and me - Guevarra, Mila (Mandaluyong City : OMF Literature Inc, 1997)
Grandma and Me is a story of a 4 year old Bea left in the care of a relative. She hasn't seen her parents for a long time. Bea tells us, "My Mommy went to Saudi Arabia. My Daddy lives in another house."
Keywords: Relative stories